Clinical Outcomes After Catheter Ablation in Patients With Structural Heart Disease and Ventricular Fibrillation - Kenji Hashimoto; Samual Turnbull; Saurabh Kumar (Journal of Cardiovascular Electrophysiology, 2026)
ABSTRACT Introduction In patients with ischemic cardiomyopathy (ICM), recurrent VF may be treated with catheter ablation by targeting triggering premature ventricular complexes (PVCs) and/or ventricular scar homogenization. Data on optimal ablation strategies in patients with non‐ischemic cardiomyopathy (NICM) remain limited. This study aimed to compare ablation strategies and outcomes in patients with recurrent VF due to ICM versus NICM. Methods and Results We retrospectively analyzed consecutive patients with structural heart disease and recurrent VF undergoing catheter ablation. Catheter ablation was performed, including targeting the triggering and/or clinically frequent PVC, targeting any inducible ventricular tachycardia, and/or scar homogenization. Procedural characteristics, arrhythmogenic substrate features, and post‐ablation clinical outcomes were compared between ICM and NICM groups. Forty‐five patients were included (17 ICM, 28 NICM; mean age 60 ± 15 years; 87% male). PVC ablation was performed in 42% of ICM and 39% of NICM patients, while scar homogenization was undertaken in 76% and 57%, respectively. Left ventricular scar burden, assessed by bipolar and unipolar voltage mapping, was significantly greater in the ICM, whereas the prevalence of abnormal Purkinje potentials was similar between groups. VF‐free survival after multiple procedures did not differ between groups, with estimated 1‐year rates of 87 ± 9% in ICM and 85 ± 8% in NICM (log‐rank p = 0.93). Conclusions In patients with NICM and recurrent VF, catheter ablation targeting arrhythmogenic substrate—including unipolar low‐voltage regions—combined with PVC ablation yields outcomes comparable to those in ICM, supporting this approach as a reasonable treatment strategy.